2023
DOI: 10.3389/fneur.2023.1078151
|View full text |Cite
|
Sign up to set email alerts
|

Novel compound heterozygous mutations of LAMA2-limb–girdle muscular dystrophy: A case report and literature review

Abstract: The laminin α2 (LAMA2) gene pathogenic variants can lead to limb–girdle muscular dystrophy (known as LGMDR23), which is rarely reported and characterized by proximal weakness in the limbs. We present the case of a 52-year-old woman who gradually developed weakness in both lower extremities since the age of 32 years. Magnetic resonance imaging (MRI) brain showed symmetrical sphenoid wings-like white matter demyelination in bilateral lateral ventricles. Electromyography showed quadriceps muscle damage on the bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This variant was mainly detected in the compound heterozygous state ( 12 - 14 ). The c.2749 + 2dup is a splicing variant inherited from the mother and has been reported in previous studies ( 15 , 16 ). The splice donor site duplication (c.2749 + 2dup) may lead to splicing abnormalities.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…This variant was mainly detected in the compound heterozygous state ( 12 - 14 ). The c.2749 + 2dup is a splicing variant inherited from the mother and has been reported in previous studies ( 15 , 16 ). The splice donor site duplication (c.2749 + 2dup) may lead to splicing abnormalities.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, diagnosis requires muscle biopsy, immunohistochemical staining, or genetic testing. It was reported that there was no merosin staining in MDC1A, but low levels of residual merosin can be detected in LGMDR23 ( 15 , 19 ). Unfortunately, muscle biopsy and immunohistochemistry staining had not been performed in this case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations